Voices Unveiled: Navigating NNESTs’ Beliefs on Pronunciation Teaching － A Systematic Review - Wang, Juan; Binti Ahmad, Norhakimah Khaiessa; Jamil, Halimah; Darmi, Ramiaida (Forum for Linguistic Studies, 2024)
Pronunciation instruction is crucial to English language teaching, significantly impacting communicative competence and language acquisition. In this context, in-service non-native English-speaking teachers (NNESTs) play a pivotal role, although their beliefs regarding pronunciation teaching practices are diverse and complex. This systematic review, conducted in accordance with the PRISMA statement, examines 22 peer-reviewed papers published between 2014 and 2023 to thoroughly explore these beliefs. The reviewed studies predominantly utilized qualitative methods to explore teachers’ perceptions and teaching approaches, and four key themes emerge. First, NNESTs emphasize the importance of pronunciation for communicative competence, shifting focus from native-like pronunciation to intelligibility. Second, pedagogical approaches vary, with many teachers still relying on traditional methods such as drills, despite a growing interest in integrating pronunciation into communicative tasks like role-plays and discussions. Third, significant challenges hinder effective pronunciation instruction, including inadequate teacher training, time constraints, and a lack of suitable teaching materials. Teachers often resort to traditional methods due to these limitations, despite recognizing the need for more interactive strategies. Finally, factors such as teachers’ linguistic backgrounds, sociocultural expectations, and institutional contexts shape their instructional practices. The review emphasizes the need for targeted professional development and institutional policies that support pronunciation teaching. Addressing these issues is crucial for enhancing pronunciation instruction and supporting NNESTs in diverse educational settings.